Preparation method of catalyst layer for growing carbon nano tube on surface of glass fiber

Through chemical self-assembly and Fenton reaction, the compact catalytic layer is formed, and the problems of low density and insufficient adhesion strength of the catalytic layer of carbon nanotube modified glass fiber in the prior art are solved, and high-density carbon nanotube growth and good adhesion are achieved. Suitable for low-cost mass production, enhancing the mechanical properties of glass fibers.

CN119241093AInactive Publication Date: 2025-01-03CHINA BUILDING MATERIALS ACADEMY CO LTD

Patent Information

Application Number
CN202411610237.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing catalytic layer preparation method for modified glass fibers of carbon nanotubes has problems such as low density of the catalytic layer, low dependence strength, high cost and complex process, making it difficult to achieve mass production, and traditional methods cannot achieve high-density carbon nanotubes. Grow and good attachment.

Method used

The method of producing a tight catalytic layer by chemical self-assemblying precursor layer and Fenton reaction is adopted to produce a tight catalytic layer. By dissolving the divalent nickel salt in deionized water, adding organic ammonium salt and adjusting the pH, forming a self-assembly complex solution and applying it to glass fibers. The surface is carried out in the hydrogen peroxide solution to remove organic components and form a tight catalytic layer, which is suitable for low-cost continuous production.

Benefits of technology

A method of growing carbon nanotubes at high density on the surface of glass fibers is realized, with high compatibility and high customization, and the carbon nanotube content can reach 0.1 wt%-40 wt%, which enhances the mechanical properties of glass fibers and improves carbon nanotubes. Adhesion is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005130748030000011
    Figure HDA0005130748030000011
  • Figure HDA0005130748030000012
    Figure HDA0005130748030000012
  • Figure HDA0005130748030000021
    Figure HDA0005130748030000021
Patent Text Reader

Abstract

The invention relates to a preparation method of a catalyst layer for growing a carbon nano tube on the surface of glass fiber, which comprises the following steps: preparing a chemical self-assembly precursor layer: dissolving bivalent nickel salt into deionized water to obtain a mixed solution, adding organic ammonium salt into the mixed solution, then adjusting the pH value to be alkalescent to obtain a self-assembly complexing solution, and carrying out chemical self-assembly on the self-assembly complexing solution to obtain the chemical self-assembly precursor layer; coating the self-assembly complexing solution on the surface of the glass fiber to obtain the glass fiber coated with a self-assembly precursor layer; hydrogen peroxide is added into the glass fiber coated with the self-assembly precursor layer, a Fenton reaction is generated, organic components in the chemical self-assembly precursor layer are removed, and the glass fiber with the surface coated with the catalyst layer is obtained. The method is simple in preparation process, short in technological process and suitable for low-cost continuous production; the prepared catalyst layer has high compatibility with various types of carbon nanotubes grown in situ, high-density growth of the carbon nanotubes is realized, and the adhesion strength is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of carbon nanotube modified glass fiber, in particular to a method for preparing a catalytic layer for growing carbon nanotubes on the surface of glass fiber. Background Art

[0002] Glass fiber (GF) is a widely used inorganic non-metallic material with high insulation, high heat resistance and good mechanical strength. It is often used to manufacture various composite materials. However, it is currently facing problems such as single function and poor interface compatibility of composite materials. Carbon nanotubes (CNT) are a new type of carbon material with unique physical, chemical and mechanical properties. They are considered to be good functional modifiers for traditional fiber materials. Studies have shown that the composite of carbon nanotubes and glass fibers can significantly improve the mechanical properties of glass fibers and give them electromagnetic functionality. However, traditional mechanical mixing or physical adsorption methods to modify the surface of glass fibers can only achieve very limited performance improvements. Only when carbon nanotubes are grown in situ on the surface of glass fibers can a good functional modification effect be achieved.

[0003] The key to the preparation of in-situ grown carbon nanotube-modified glass fiber lies in the design of the catalytic layer on the glass fiber surface. Generally speaking, the tighter the catalytic layer and the glass fiber are combined, the better the adhesion of the grown carbon nanotubes is, and the greater the improvement in the performance of the glass fiber. The existing methods for preparing carbon nanotube-modified glass fiber are as follows:

[0004] Floating chemical vapor method: The catalyst precursor is introduced into the reaction chamber, gasified and suspended in the gas phase. The catalyst interacts with the carbon-containing gas to deposit carbon nanotubes on the glass fiber substrate. The catalyst particles float freely in the reaction chamber, which is more conducive to the isotropic growth of carbon nanotubes. The carbon nanotubes grown by the floating catalyst method are relatively controllable and can also obtain a higher content, but there is only intermolecular van der Waals force between the carbon nanotubes and the glass fiber, which makes it very easy for the carbon nanotubes to detach from the glass fiber surface, and it is not suitable for mass production.

[0005] Chemical grafting method for growing carbon nanotubes: Through surface oxidation, sulfuric acid treatment, plasma treatment and other methods, a functionalized substrate containing active groups is generated on the surface of the glass fiber, and then the glass fiber and carbon nanotubes containing functional groups (such as carboxylated carbon nanotubes) are combined by chemical bonding to obtain carbon nanotube-modified glass fibers. The chemical grafting method for growing carbon nanotubes has very high requirements for the substrate. The functional group density of the substrate determines the growth density of the carbon nanotubes, but the preparation of highly functionalized glass fibers is extremely difficult, and the utilization efficiency of functional groups is not high. This method can only achieve the growth of carbon nanotubes at a relatively low density, and the carbon nanotube content generally does not exceed 5wt%.

[0006] Currently, the main methods for preparing catalytic layers are based on simple impregnation or chemical deposition physical coating methods. There are problems such as low density of the catalytic layer, low adhesion strength, high cost, and complex process, making it difficult to achieve mass production. Summary of the invention

[0007] The main purpose of the present invention is to provide a method for preparing a catalytic layer for growing carbon nanotubes on the surface of glass fiber, which can achieve high-density carbon nanotube growth and has high attachment strength.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a catalytic layer for growing carbon nanotubes on the surface of glass fiber comprises the following steps:

[0010] Chemical self-assembly precursor layer preparation:

[0011] Dissolving a divalent nickel salt in deionized water to obtain a mixed solution, adding an organic ammonium salt to the mixed solution, adjusting the pH to be weakly alkaline to obtain a self-assembly complex solution, and applying the self-assembly complex solution to a surface of a glass fiber to obtain a glass fiber coated with a self-assembly precursor layer;

[0012] Preparation of compact catalyst layer:

[0013] A hydrogen peroxide solution is added to the glass fiber coated with the self-assembly precursor layer to generate a Fenton reaction, thereby removing the organic components in the chemical self-assembly precursor layer and obtaining the glass fiber with a catalytic layer coated on the surface.

[0014] The concentration of the divalent nickel salt in deionized water is 0.02-0.2 mol / L, and the molar ratio of the organic ammonium salt to the nickel salt is 4:1.

[0015] Furthermore, the compact catalytic layer on the surface of the glass fiber also includes at least one element of Zn, Mn, Fe, Cu, Co, Si and Al, each element is in its corresponding oxidation state, with Fe 2+ , Fe 3+ , Cu 2+ 、Ni 2+ 、Co 2+ 、Co 3+ 、Al 3+ or reduced to a simple form by a reducing gas;

[0016] The mixed solution contains a metal salt solution of at least one element of Zn, Mn, Fe, Cu, Co, and Al;

[0017] When the compact catalytic layer contains Si element, the glass fiber coated with the self-assembly precursor layer is further coated with a methylsiloxane ethanol solution with a concentration of 50-60 wt %.

[0018] The concentration of the metal salt solution is 0.01-0.1 mol / L.

[0019] The metal salt solution is a nitrate solution, a sulfate solution or a chloride solution;

[0020] The concentration of the hydrogen peroxide solution is 1 wt%-30 wt%.

[0021] The nickel salt is nickel (II) nitrate, nickel (II) chloride, nickel (II) sulfate or nickel (II) acetate.

[0022] The organic ammonium salt is ammonium oxalate, ammonium acetate, ammonium acrylate, ammonium citrate, ammonium benzoate, ammonium tartrate or hexadecyltrimethylammonium bromide;

[0023] The solution for adjusting pH is aqueous ammonia, the concentration of the aqueous ammonia is 28-32 wt%, and the pH is 8-9;

[0024] The glass fiber is alkali-free glass fiber, S-glass fiber, quartz fiber or high-silica fiber.

[0025] The first preset time for the glass fiber to stay in the self-assembly complex solution is 60-180s;

[0026] The self-assembly complex solution is applied to the glass fiber surface, including coating in the form of the following chemical self-assembly:

[0027] Using a spool pulling method, the glass fiber passes through a pool of self-assembly complex solution at a constant rate of 1-3 m / min and for a first preset time;

[0028] Alternatively, the chopped glass fibers are placed in a filter screen, directly immersed in a pool of self-assembly complex solution, and taken out after staying for a first preset time;

[0029] Drying the glass fiber coated with the self-assembly complex solution in hot air at 40-80° C. for 10-15 minutes to obtain a glass fiber coated with a self-assembly precursor layer;

[0030] When the compact catalytic layer contains Si element, the glass fiber coated with the self-assembled precursor layer is coated with a 50-60wt% methylsiloxane ethanol solution in the same manner as the method of applying the self-assembled complex solution to the surface of the glass fiber;

[0031] The glass fiber coated with the self-assembly precursor layer stays in the methylsiloxane ethanol solution for 30-60 seconds.

[0032] The second preset time for the glass fiber coated with the self-assembly precursor layer to stay in the hydrogen peroxide solution is 120s-180s;

[0033] The adding of hydrogen peroxide to the glass fiber coated with the self-assembly precursor layer comprises the following coating method:

[0034] The glass fiber coated with the self-assembled precursor layer is passed through a hydrogen peroxide solution pool at a constant speed of 1-3 m / min and for a second preset time by a bobbin pulling method;

[0035] Alternatively, the chopped glass fiber coated with the self-assembly precursor layer is placed in a filter screen, directly immersed in the hydrogen peroxide solution, and taken out after staying for a second preset time;

[0036] The glass fiber after Fenton reaction is dried in hot air at 40-80° C. for 10-15 minutes to obtain a glass fiber with a catalytic layer coated on the surface.

[0037] The present invention also provides a method for preparing in-situ grown carbon nanotube modified glass fiber. The catalytic layer is prepared according to the preparation method, and then carbon nanotubes are in-situ grown on the surface of the catalytic layer to obtain in-situ grown carbon nanotube modified glass fiber.

[0038] The method for in-situ growth of carbon nanotubes is chemical vapor deposition, flame synthesis, arc discharge or high-pressure carbon monoxide synthesis; the content of carbon nanotubes is 0.5-40wt%.

[0039] By means of the above technical solution, the present invention has at least the following advantages:

[0040] 1. The present invention provides a method for setting a compact catalytic layer on the surface of glass fiber, which is used for in-situ growth of carbon nanotubes on the surface of glass fiber. The preparation process is simple and the process flow is short. It does not involve complex treatment methods such as high pressure, vacuum, and coating, and is suitable for low-cost continuous production.

[0041] 2. The catalytic layer of the present invention has high compatibility with various types of in-situ grown carbon nanotubes and is highly customized. The carbon nanotube-modified glass fiber prepared by the method of the present invention has a carbon nanotube content between 0.1wt% and 40wt%, preferably between 0.5wt% and 40wt%, achieving high-density carbon nanotube growth;

[0042] 3. The compact catalytic layer can provide good protection for the original glass fiber. The in-situ grown carbon nanotubes on the surface of the glass fiber will not damage the fiber substrate and have high adhesion, which can effectively enhance the mechanical properties of the glass fiber.

[0043] 4. The present invention adds at least one element among Zn, Mn, Fe, Cu, Co, Si and Al to the catalytic layer generated on the surface of the glass fiber to improve the catalytic effect of the Ni-based catalytic layer, and properly isolates the catalyst from the substrate to protect the glass fiber substrate from damage in subsequent processes.

[0044] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a scanning electron microscope (SEM) image of high-silica fiber with 10 wt% carbon nanotube content grown in situ provided in Example 1 of the present invention;

[0046] Figure 2 is a scanning electron microscope (SEM) image of the alkali-free glass fiber with 30 wt% carbon nanotube content grown in situ provided by Example 3 of the present invention;

[0047] Figure 3 is a scanning electron microscope (SEM) image of an S-glass fiber with a carbon nanotube content of 40 wt% grown in situ provided in Example 4 of the present invention;

[0048] Figure 4 It is a scanning electron microscope (SEM) image of the in-situ grown high-silica fiber with 10 wt% carbon nanotube content provided by the comparative example of the present invention. DETAILED DESCRIPTION

[0049] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.

[0050] The present invention provides a method for preparing a compact catalytic layer on the surface of a glass fiber for growing carbon nanotubes, comprising two steps of chemically self-assembling a precursor layer and generating a compact catalytic layer through a Fenton reaction:

[0051] Chemical self-assembly precursor layer preparation:

[0052] Dissolve an appropriate amount of divalent nickel salt in deionized water. The nickel salt can be any salt with suitable solubility, such as nickel (II) nitrate, nickel (II) chloride, nickel (II) sulfate, nickel (II) acetate, etc. After the dissolution is completed, add an appropriate amount of organic ammonium salt according to a specific ratio. Similarly, the organic ammonium salt can also be any salt with suitable solubility, such as ammonium oxalate, ammonium acetate, ammonium acrylate, ammonium citrate, ammonium benzoate, ammonium tartrate, hexadecyltrimethylammonium bromide (CTAB), etc., adjust the pH to a weak alkaline state, and Ni (II) will form a coordination with free NH3 in the solution. NH3 also combines with the free hydroxyl groups exposed on the surface of the glass fiber through hydrogen bonding, so Ni (II) can be bridged by NH3 and coated on the surface of the glass fiber in the form of chemical self-assembly to form a precursor layer.

[0053] Preparation of compact catalyst layer:

[0054] Then, a proper amount of hydrogen peroxide (H2O2) solution is added to the glass fiber forming the precursor layer to produce a Fenton reaction, remove the organic components in the precursor, and completely anchor the catalytic metal on the fiber surface, completing the step of coating the catalytic layer on the glass fiber surface. It is also possible to add one or two elements of Zn, Mn, Fe, Cu, Co, Si, and Al to the catalytic layer generated on the glass fiber surface in order to improve the catalytic effect of the Ni-based catalytic layer, to properly isolate the catalyst from the glass fiber substrate, and to protect the glass fiber substrate from damage during subsequent processes. Before the in-situ growth of carbon nanotubes is performed, the metal elements in the catalytic layer on the glass fiber surface can be in their corresponding oxidation states, for example, Fe 2+ , Fe 3+ , Cu 2+ 、Ni 2+ 、Co 2+ 、Co 3+ 、Al 3+ The catalyst layer of the present invention can be applied in an off-line (i.e., intermittent) manner, which is suitable for coating chopped fibers, or in an on-line (i.e., using a bobbin traction method) manner through a specific transmission mechanism, which is suitable for coating continuous glass fibers.

[0055] The substrate involved in the invention can be various types of glass fibers currently available on the market, such as alkali-free glass fiber, S-glass fiber, quartz fiber, high-silica fiber, etc.

[0056] The in-situ growth of carbon nanotubes produced by the present invention can be produced by a variety of existing methods, such as thermal / plasma enhanced chemical vapor deposition, flame synthesis, arc discharge, high pressure carbon monoxide synthesis, etc., which are not limited here. However, in the specific implementation process, the present invention preferably uses chemical vapor deposition because this method makes it easier to control the in-situ carbon nanotube growth process.

[0057] The present invention will be further described below by means of specific embodiments:

[0058] Embodiment 1:

[0059] A method for arranging a FeNi catalytic layer on the surface of a high-silica fiber and for in-situ growth of 10wt% carbon nanotubes.

[0060] 14.5g nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 12.1g ferric nitrate nonahydrate (Fe(NO3)3·9H2O) were added to 1000mL deionized water until they were dissolved into a transparent solution with a nickel nitrate concentration of 0.05mol / L and a ferric nitrate concentration of 0.03mol / L; 72.9g hexadecyltrimethylammonium bromide (CTAB) was then added to the transparent solution until it was completely dissolved, and then an appropriate amount of 32wt% ammonia water was added to the solution until the pH of the solution was adjusted to 8.5 to obtain a self-assembled complex solution. According to different needs, the amount of the above materials can also be proportionally increased or decreased to ensure that the concentration of the components remains unchanged to meet actual needs.

[0061] The high silica fiber is placed in the self-assembly complex solution for 90 seconds in an appropriate manner, and the complex components in the self-assembly complex solution are introduced into the fiber surface by the self-assembly method:

[0062] The continuous high-silica fiber was pulled by a bobbin at a constant rate of 3 m / min and passed through a self-assembly complex solution pool with a length of 4.5 m in 90 s; the short-cut high-silica fiber was placed in a filter, directly immersed in the self-assembly complex solution pool, and taken out after staying for 90 s.

[0063] Then, the high-silica fiber coated with the self-assembly complex solution was dried under hot air at 60° C. for 10 min to obtain the high-silica fiber coated with the self-assembly precursor layer.

[0064] The high-silica fiber coated with the self-assembled precursor layer obtained above is placed in a 10wt% hydrogen peroxide solution for 180s in an appropriate manner to produce a Fenton reaction, remove the organic components in the precursor, and completely anchor the catalytic metal on the surface of the glass fiber. The step of coating the catalytic layer on the surface of the high-silica fiber includes:

[0065] The continuous high-silica fiber was pulled through a hydrogen peroxide solution pool with a length of 4.5 m at a constant rate of 1.5 m / min for 180 s by a bobbin traction method; the short-cut high-silica fiber was placed in a filter screen, directly immersed in the hydrogen peroxide solution pool, and taken out after staying for 180 s.

[0066] The high-silica fiber after the Fenton reaction was dried in hot air at 60° C. for 10 minutes to obtain a high-silica fiber with a compact catalytic layer.

[0067] The compact catalytic layer obtained by the above method mainly consists of Ni and Fe metal oxides, with the atomic ratio of Ni to Fe being 1:1. Carbon nanotubes with a content of 10 wt% are in-situ grown on the compact catalytic layer by chemical vapor deposition.

[0068] like Figure 1 As shown, from the SEM image of the in-situ grown high-silica fiber with a carbon nanotube content of 10 wt %, it can be seen that after the high-silica fiber is treated by the method of this embodiment, a catalytic layer sufficient to support carbon nanotubes with a content of 10 wt % can be generated on its surface.

[0069] Embodiment 2:

[0070] The invention discloses a method for setting a NiCo catalytic layer on the surface of a quartz fiber and adding an Al2O3 protective agent, and is used for in-situ growth of 5wt% carbon nanotubes.

[0071] 18.9g nickel chloride hexahydrate (NiCl2·6H2O), 14.6g cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 3.42g aluminum sulfate (Al2(SO4)3) are added to 1000mL deionized water until they are dissolved into a transparent solution with a nickel chloride concentration of 0.08mol / L, a cobalt nitrate concentration of 0.05mol / L and an aluminum sulfate concentration of 0.01mol / L; 77.6g ammonium citrate is then added to the transparent solution until it is completely dissolved, and an appropriate amount of 30wt% ammonia water is added to the solution until the pH of the solution is adjusted to 8 to obtain a self-assembled complex solution. According to different needs, the amount of the above materials can also be proportionally enlarged or reduced to ensure that the concentration of the components remains unchanged to meet actual needs.

[0072] The quartz fiber is placed in the self-assembly complex solution for 60 seconds in an appropriate manner, and the complex components in the self-assembly complex solution are introduced into the fiber surface by the self-assembly method:

[0073] The continuous quartz fiber was pulled by a bobbin at a constant rate of 3 m / min for 60 s through a self-assembly complex solution pool of 3 m in length; the short-cut quartz fiber was placed in a filter, directly immersed in the self-assembly complex solution pool, and taken out after staying for 60 s.

[0074] Then, the quartz fiber coated with the self-assembly complex solution was dried in hot air at 40° C. for 12 minutes to obtain a quartz fiber coated with a self-assembly precursor layer.

[0075] The quartz fiber coated with the self-assembled precursor layer obtained above is placed in a 5wt% hydrogen peroxide solution for 120s in an appropriate manner to produce a Fenton reaction, remove the organic components in the precursor, and completely anchor the catalytic metal on the fiber surface. The step of coating the catalytic layer on the surface of the quartz fiber includes:

[0076] The continuous quartz fiber was pulled through a 6-m-long hydrogen peroxide solution pool at a constant rate of 3 m / min for 120 s by a bobbin traction method; the short-cut quartz fiber was placed in a filter screen, directly immersed in the hydrogen peroxide solution pool, and taken out after staying for 120 s.

[0077] The quartz fiber treated by Fenton reaction was dried in hot air at 60° C. for 12 minutes to obtain a quartz fiber with a compact catalytic layer.

[0078] The compact catalyst layer obtained by the above method is mainly composed of metal oxides of Ni, Co and Al, and the atomic ratio of Ni, Co and Al is 1:1:1, wherein Ni and Co are catalytic components and Al is a protective component. Carbon nanotubes with a content of 5wt% are in situ grown on the compact catalyst layer by a high-pressure carbon monoxide synthesis method.

[0079] Embodiment 3:

[0080] The invention discloses a method for arranging a FeNiCo catalytic layer on the surface of an alkali-free glass fiber and adding a Si-based protective agent, and is used for in-situ growth of 30wt% carbon nanotubes.

[0081] Add 14.5g nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 4.74g cobalt chloride hexahydrate (CoCl2·6H2O), and 24.4g ferric nitrate nonahydrate (Fe(NO3)3·9H2O) to 1000mL deionized water until dissolved into a transparent solution with a nickel nitrate concentration of 0.05mol / L, a cobalt chloride concentration of 0.02mol / L, and a ferric nitrate concentration of 0.06mol / L; then add 17.8g ammonium acrylate to the transparent solution until it is completely dissolved. Add an appropriate amount of 28wt% ammonia water to the solution until the pH of the solution is adjusted to 9 to obtain a self-assembled complex solution. According to different needs, the amount of the above materials can also be proportionally increased or decreased to ensure that the concentration of the components remains unchanged to meet actual needs.

[0082] The alkali-free glass fiber is placed in the self-assembly complex solution for 120 seconds in an appropriate manner, and the complex components in the self-assembly complex solution are introduced into the fiber surface by the self-assembly method:

[0083] The continuous alkali-free glass fiber was pulled by a spool at a constant rate of 2 m / min and passed through a self-assembly complex solution pool with a length of 3 m for 120 s; the short alkali-free glass fiber was placed in a filter, directly immersed in the self-assembly complex solution pool, and taken out after staying for 120 s.

[0084] The alkali-free glass fiber coated with the self-assembly complex solution was then dried in hot air at 60°C for 10 min, and then the alkali-free glass fiber was allowed to remain in a 50wt% methylsiloxane ethanol solution for 30 s in the same manner, and then dried again in hot air at 50°C for 12.5 min. After drying, an alkali-free glass fiber coated with a self-assembly precursor layer was obtained.

[0085] The alkali-free glass fiber coated with the self-assembled precursor layer obtained above is placed in a 20wt% hydrogen peroxide solution for 120s in an appropriate manner to produce a Fenton reaction, remove the organic components in the precursor, and completely anchor the catalytic metal on the fiber surface. The step of coating the catalytic layer on the surface of the alkali-free glass fiber includes:

[0086] The continuous alkali-free glass fiber was pulled through a hydrogen peroxide solution pool with a length of 4 m at a constant rate of 2 m / min for 120 s by a spool traction method; the short alkali-free glass fiber was placed in a filter, directly immersed in the hydrogen peroxide solution pool, and taken out after staying for 120 s.

[0087] The alkali-free glass fiber treated by Fenton reaction was dried in hot air at 60° C. for 12.5 min, and then annealed in a hydrogen-argon mixed gas with a hydrogen volume content of 5% at 400° C. for 10 min to obtain an alkali-free glass fiber with a compact catalytic layer.

[0088] The compact catalyst layer obtained by the above method mainly consists of metal elements of Ni, Co, and Fe, and contains SiO2 protective components, and the atomic ratio of Ni:Co:Fe is 5:2:6. Carbon nanotubes with a content of 30wt% are in-situ grown on the compact catalyst layer by chemical vapor deposition.

[0089] like Figure 2 As shown, from the SEM image of the in-situ grown alkali-free glass fiber with a carbon nanotube content of 30 wt %, it can be seen that after the alkali-free glass fiber is treated by the method of this embodiment, a catalytic layer sufficient to support 30 wt % carbon nanotubes can be generated on its surface.

[0090] Embodiment 4:

[0091] A method for arranging a FeNiCo catalytic layer on the surface of an S-glass fiber and adding a Si-based protective agent is provided, and is used for in-situ growth of 40wt% carbon nanotubes.

[0092] Add 52.7g nickel sulfate hexahydrate (NiSO4·6H2O), 5.26g cobalt sulfate hexahydrate (Co(NO3)2·6H2O), and 40.3g ferric nitrate nonahydrate (Fe(NO3)3·9H2O) to 1000mL deionized water until dissolved into a transparent solution with a nickel nitrate concentration of 0.2mol / L, a cobalt chloride concentration of 0.02mol / L, and a ferric nitrate concentration of 0.1mol / L; then add 99.2g ammonium oxalate monohydrate ((NH4)2C2O4·H2O) to the transparent solution until it is completely dissolved. Add an appropriate amount of 32wt% ammonia water to the solution until the pH of the solution is adjusted to 8.5 to obtain a self-assembled complex solution. According to different needs, the amount of the above materials can also be proportionally enlarged or reduced to ensure that the concentration of the components remains unchanged to meet actual needs.

[0093] The S-glass fiber is kept in the self-assembly complex solution for 180 seconds in an appropriate manner, and the complex components in the self-assembly complex solution are introduced into the fiber surface by the self-assembly method:

[0094] The continuous S-glass fiber was pulled by a spool at a constant rate of 1 m / min and passed through a self-assembly complex solution pool with a length of 3 m for 180 s; the short-cut S-glass fiber was placed in a filter and directly immersed in the self-assembly complex solution pool and taken out after staying for 180 s.

[0095] The S-glass fiber coated with the self-assembly complex solution was then dried in hot air at 70°C for 15 minutes, and then the S-glass fiber was placed in a 55wt% methylsiloxane ethanol solution for 60 seconds in the same manner, and then dried again in hot air at 80°C for 10 minutes. After drying, an S-glass fiber coated with a self-assembly precursor layer was obtained.

[0096] The S-glass fiber coated with the self-assembled precursor layer obtained above is placed in a 30wt% hydrogen peroxide solution for 180s in an appropriate manner to produce a Fenton reaction, remove the organic components in the precursor, and completely anchor the catalytic metal on the fiber surface. The step of coating the catalytic layer on the surface of the S-glass fiber includes:

[0097] The continuous S-glass fiber was pulled through a hydrogen peroxide solution pool with a length of 3 m at a constant rate of 1 m / min for 180 s by a spool traction method; the short-cut S-glass fiber was placed in a filter screen, directly immersed in the hydrogen peroxide solution pool, and taken out after staying for 180 s.

[0098] The S-glass fiber treated by Fenton reaction was dried in hot air at 70° C. for 15 minutes, and then annealed in a hydrogen-argon mixed gas with a hydrogen volume content of 10% at 450° C. for 15 minutes to obtain an S-glass fiber with a compact catalytic layer.

[0099] The compact catalyst layer obtained by the above method mainly consists of metal elements of Ni, Co, and Fe, and contains SiO2 protective components, and the atomic ratio of Ni, Co, and Fe is 15:2:6. Using the arc discharge method, carbon nanotubes with a content of 40wt% are in situ grown on the compact catalyst layer.

[0100] like Figure 3 As shown, from the SEM image of the in-situ grown S-glass fiber with a carbon nanotube content of 40 wt %, it can be seen that after the S-glass fiber is treated by the method of this embodiment, a catalytic layer sufficient to support carbon nanotubes with a content of 40 wt % can be generated on its surface.

[0101] Embodiment 5:

[0102] A method for providing a Ni catalytic layer on the surface of an S-glass fiber and for in-situ growth of 0.5wt% carbon nanotubes.

[0103] Add 5.8g nickel nitrate hexahydrate (Ni(NO3)2·6H2O) to 1000mL deionized water until it dissolves into a transparent solution with a nickel nitrate concentration of 0.02mol / L; then add 11.4g ammonium oxalate monohydrate ((NH4)2C2O4·H2O) to the transparent solution until it is completely dissolved. Add an appropriate amount of 32wt% ammonia water to the solution until the pH of the solution is adjusted to 8.5 to obtain a self-assembled complex solution. According to different needs, the amount of the above materials can also be proportionally increased or decreased to ensure that the concentration of the components remains unchanged to meet actual needs.

[0104] The S-glass fiber is kept in the self-assembly complex solution for 60 seconds in an appropriate manner, and the complex components in the self-assembly complex solution are introduced into the fiber surface by the self-assembly method:

[0105] The continuous S-glass fiber was pulled by a spool at a constant rate of 3 m / min for 60 s through a self-assembly complex solution pool of 3 m in length; the short-cut S-glass fiber was placed in a filter, directly immersed in the self-assembly complex solution pool, and taken out after staying for 60 s.

[0106] Then the S-glass fiber coated with the self-assembly complex solution was dried under hot air at 60° C. for 10 min. After drying, the S-glass fiber coated with the self-assembly precursor layer was obtained.

[0107] The S-glass fiber coated with the self-assembled precursor layer obtained above is placed in a 1wt% hydrogen peroxide solution for 120s in an appropriate manner to produce a Fenton reaction, remove the organic components in the precursor, and completely anchor the catalytic metal on the fiber surface. The step of coating the catalytic layer on the surface of the S-glass fiber includes:

[0108] The continuous S-glass fiber was pulled through a hydrogen peroxide solution pool of 3 m in length at a constant rate of 3 m / min for 60 s by a bobbin traction method; the short-cut S-glass fiber was placed in a filter screen, directly immersed in the hydrogen peroxide solution pool, and taken out after staying for 60 s.

[0109] The S-glass fiber treated by Fenton reaction was dried in hot air at 60° C. for 10 min, and then annealed in a hydrogen-argon mixed gas with a hydrogen volume content of 10% at 450° C. for 15 min to obtain an S-glass fiber with a compact catalytic layer.

[0110] The compact catalytic layer obtained by the above method is mainly composed of a metal element of Ni. A high-pressure carbon monoxide method is used to in-situ grow carbon nanotubes with a content of 0.5 wt % on the compact catalytic layer.

[0111] Comparative Example 1:

[0112] A method for arranging a FeNi catalytic layer on the surface of a high-silica fiber and for in-situ growth of 10wt% carbon nanotubes.

[0113] In this example, no organic ammonium salt was added, and no Fenton reaction treatment was performed. The other conditions were the same as those in Example 1. A FeNi catalyst layer was set on the surface of the high-silica fiber by a simple impregnation method, and used to grow 10wt% carbon nanotubes in situ. The specific method is as follows:

[0114] 14.5g nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 12.1g ferric nitrate nonahydrate (Fe(NO3)3·9H2O) were added to 1000mL deionized water until they were dissolved into a transparent solution with a nickel nitrate concentration of 0.05mol / L and a ferric nitrate concentration of 0.03mol / L to obtain an impregnation solution. According to different needs, the amount of the above materials can also be proportionally increased or decreased to ensure that the component concentration remains unchanged to meet actual needs.

[0115] The high silica fiber is kept in the impregnation solution for 90 seconds in an appropriate manner to introduce the precursor components in the impregnation solution into the fiber surface:

[0116] The continuous high-silica fiber was pulled through an impregnation solution pool with a length of 4.5 m at a constant rate of 3 m / min for 90 s by a bobbin traction method; the short-cut high-silica fiber was placed in a filter screen, directly immersed in the impregnation solution, and taken out after staying for 90 s.

[0117] Then, the high-silica fiber coated with the impregnation solution was dried under hot air at 60° C. for 10 minutes to obtain a high-silica fiber coated with an impregnation precursor layer.

[0118] The impregnation precursor layer obtained by the above method mainly consists of Ni and Fe metal oxides, and the atomic ratio of Ni to Fe is 1:1. Carbon nanotubes with a content of 10wt% are in-situ grown on the impregnation precursor layer by chemical vapor deposition.

[0119] like Figure 4 As shown, from the SEM image of high-silica fiber with an in-situ growth content of 10wt% carbon nanotubes on the impregnated precursor layer, it can be seen that after the high-silica fiber is treated by the comparative example method, compared with the high-silica fiber treated by adding organic ammonium salt and Fenton reaction using a self-assembled complex solution, the carbon nanotubes generated in situ on the surface have obvious agglomeration and peeling phenomena, indicating that the adhesion force of the carbon nanotubes based on the impregnated precursor layer is much weaker than the adhesion force generated by the compact precursor layer proposed in the present invention. Therefore, the method proposed in the present invention of coating the catalyst layer on the glass fiber surface by self-assembly method and directly growing carbon nanotubes on the catalyst layer has obvious advantages.

[0120] The method of the invention has good versatility on various glass fiber substrates and can prepare a series of carbon nanotube-modified glass fibers with carbon nanotube contents ranging from 0.1 wt% to 40 wt%.

[0121] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a catalytic layer for growing carbon nanotubes on the surface of glass fiber, characterized in that: The following steps are involved: Chemical self-assembly precursor layer preparation: Dissolving a divalent nickel salt in deionized water to obtain a mixed solution, adding an organic ammonium salt to the mixed solution, adjusting the pH to be weakly alkaline to obtain a self-assembly complex solution, and applying the self-assembly complex solution to a surface of a glass fiber to obtain a glass fiber coated with a self-assembly precursor layer; Preparation of compact catalyst layer: A hydrogen peroxide solution is added to the glass fiber coated with the self-assembly precursor layer to generate a Fenton reaction, thereby removing the organic components in the chemical self-assembly precursor layer and obtaining the glass fiber with a catalytic layer coated on the surface.

2. The preparation method according to claim 1, characterized in that: The concentration of the divalent nickel salt in deionized water is 0.02-0.2 mol / L, and the molar ratio of the organic ammonium salt to the nickel salt is 4:

1.

3. The preparation method according to claim 2, characterized in that: The compact catalytic layer on the surface of the glass fiber also includes at least one element of Zn, Mn, Fe, Cu, Co, Si and Al, each element is in its corresponding oxidation state, with Fe 2+ , Fe 3+ , Cu 2+ 、Ni 2+ 、Co 2+ 、Co 3+ 、Al 3+ or reduced to a simple form by a reducing gas; The mixed solution contains a metal salt solution of at least one element of Zn, Mn, Fe, Cu, Co, and Al; When the compact catalytic layer contains Si element, the glass fiber coated with the self-assembly precursor layer is further coated with a methylsiloxane ethanol solution with a concentration of 50-60 wt %.

4. The preparation method according to claim 3, characterized in that: The concentration of the metal salt solution is 0.01-0.1 mol / L; The metal salt solution is a nitrate solution, a sulfate solution or a chloride solution.

5. The preparation method according to claim 1, characterized in that: The concentration of the hydrogen peroxide solution is 1 wt%-30 wt%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The nickel salt is nickel (II) nitrate, nickel (II) chloride, nickel (II) sulfate or nickel (II) acetate; The organic ammonium salt is ammonium oxalate, ammonium acetate, ammonium acrylate, ammonium citrate, ammonium benzoate, ammonium tartrate or hexadecyltrimethylammonium bromide; The solution for adjusting pH is aqueous ammonia, the concentration of the aqueous ammonia is 28-32 wt%, and the pH is 8-9; The glass fiber is alkali-free glass fiber, S-glass fiber, quartz fiber or high-silica fiber.

7. The preparation method according to claim 6, characterized in that: The first preset time for the glass fiber to stay in the self-assembly complex solution is 60-180s; The self-assembly complex solution is applied to the glass fiber surface, including coating in the form of the following chemical self-assembly: Using a spool pulling method, the glass fiber passes through a pool of self-assembly complex solution at a constant rate of 1-3 m / min and for a first preset time; Alternatively, the chopped glass fibers are placed in a filter screen, directly immersed in a pool of self-assembly complex solution, and taken out after staying for a first preset time; Drying the glass fiber coated with the self-assembly complex solution in hot air at 40-80° C. for 10-15 minutes to obtain a glass fiber coated with a self-assembly precursor layer; When the compact catalytic layer contains Si element, the glass fiber coated with the self-assembled precursor layer is coated with a methylsiloxane ethanol solution with a concentration of 50-60wt% in the same manner as the method of applying the self-assembled complex solution to the surface of the glass fiber; The glass fiber coated with the self-assembly precursor layer stays in the methylsiloxane ethanol solution for 30-60 seconds.

8. The preparation method according to claim 7, characterized in that: The second preset time for the glass fiber coated with the self-assembly precursor layer to stay in the hydrogen peroxide solution is 120s-180s; The adding of hydrogen peroxide to the glass fiber coated with the self-assembly precursor layer comprises the following coating method: The glass fiber coated with the self-assembled precursor layer is passed through a hydrogen peroxide solution pool at a constant speed of 1-3 m / min and for a second preset time by a bobbin pulling method; Alternatively, the chopped glass fiber coated with the self-assembly precursor layer is placed in a filter screen, directly immersed in the hydrogen peroxide solution, and taken out after staying for a second preset time; The glass fiber after Fenton reaction is dried in hot air at 40-80° C. for 10-15 minutes to obtain a glass fiber with a catalytic layer coated on the surface.

9. A method for preparing in-situ grown carbon nanotube modified glass fiber, characterized in that: The catalytic layer is prepared according to the preparation method described in any one of claims 1 to 8, and carbon nanotubes are then in-situ grown on the surface of the catalytic layer to obtain in-situ grown carbon nanotube modified glass fibers.

10. The preparation method according to claim 9, characterized in that: The method for in-situ growth of carbon nanotubes is chemical vapor deposition, flame synthesis, arc discharge or high-pressure carbon monoxide synthesis; the content of carbon nanotubes is 0.5-40wt%.

Citation Information

Patent Citations

  • Polyacrylonitrile fiber duplex metal complexes catalyst and preparation method thereof

    CN101362102A

  • Glass substrates having carbon nanotubes grown thereon and methods for production thereof

    CN103097039A

  • Fe-N2-C4 monatomic catalyst in-situ modified carbon fiber as well as preparation method and application thereof

    CN118273102A

  • Carbon nanotube modified fiber material as well as preparation method and application thereof

    CN118441465A

  • Glass Fiber having Metallic Coating

    GB1181046A

Cited By

  • Composite sound absorption material based on carbon nanotube modified glass fibers and preparation method and application thereof

    CN121405376A

  • Carbon nanotube modified glass fiber composite sound-absorbing material, preparation method and application thereof

    CN121405376B